2019
DOI: 10.5194/essd-11-921-2019
|View full text |Cite
|
Sign up to set email alerts
|

A unified data set of airborne cloud remote sensing using the HALO Microwave Package (HAMP)

Abstract: Abstract. Cloud properties and their environmental conditions were observed during four aircraft campaigns over the North Atlantic on 37 flights. The Halo Microwave Package (HAMP) was deployed on the German research aircraft HALO (High Altitude Long Range Research Aircraft) during these four campaigns. HAMP comprises microwave radiometers with 26 channels in the frequency range between 20 and 183 GHz and a 35 GHz cloud radar. The four campaigns took place between December 2013 and October 2016 out of Barbados … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…During the NAWDEX campaign, the German research aircraft HALO (High Altitude and LOng Range Research Aircraft) observed the cloud structure of the WCB associated with Vladiana (IOP 3) on 23 September 2016 (Schäfler et al ; Konow et al ). HALO was equipped with multiple remote‐sensing instruments and carried the HALO Microwave Package (HAMP), which includes the high‐sensitivity cloud radar MIRA‐36 (Melchiona et al ; Mech et al ).…”
Section: Methodsmentioning
confidence: 99%
“…During the NAWDEX campaign, the German research aircraft HALO (High Altitude and LOng Range Research Aircraft) observed the cloud structure of the WCB associated with Vladiana (IOP 3) on 23 September 2016 (Schäfler et al ; Konow et al ). HALO was equipped with multiple remote‐sensing instruments and carried the HALO Microwave Package (HAMP), which includes the high‐sensitivity cloud radar MIRA‐36 (Melchiona et al ; Mech et al ).…”
Section: Methodsmentioning
confidence: 99%
“…This section presents the first estimates of M from observations made during the NARVAL2 field campaign, which took place in the same area as NARVAL1 near Barbados, but in summer (Stevens et al 2019;Konow et al 2019). The observations used are derived from dropsondes released at high frequency during research flights RF03 and RF06 on 12 and 19 August 2016.…”
Section: Application To Narval2 Observationsmentioning
confidence: 99%
“…The research aircraft carries the HALO Microwave Package (HAMP), which includes the high-sensitivity cloud radar MIRA-36 (Melchiona et al, 2008;Mech et al, 2014). The downward pointing Doppler radar operates at a frequency of 35.5 GHz and reaches an expected airborne sensitivity of −38 dBZ at 5 km distance (Mech et al, 2014), which reduces to ≈ −30 dBZ at 13 km distance (Konow et al, 2019). The measured along-flight radar reflectivity Z has been post-processed, offset-corrected and corrected for aircraft attitude (Ewald et al, 2019;Konow et al, 2019) and is obtained from Konow et al (2018).…”
Section: Airborne Radar Observationsmentioning
confidence: 99%